2012
DOI: 10.1074/mcp.m111.008466
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome Comparison Between Physiological Angiogenesis and Angiogenesis in Glioblastoma

Abstract: The molecular pathways involved in neovascularization of regenerating tissues and tumor angiogenesis resemble each other. However, the regulatory mechanisms of neovascularization under neoplastic circumstances are unbalanced leading to abnormal protein expression patterns resulting in the formation of defective and often abortive tumor vessels. Because gliomas are among the most vascularized tumors, we compared the protein expression profiles of proliferating vessels in glioblastoma with those in tissues in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…Within one tumor different phenotypes like incipient proliferation of endothelial cells or sarcomatous structures are found. 77 Especially the alternatively spliced domains TNfnC 78,79 and TNfnA2 38 could be found highly up-regulated in glioma blood vessels, but also the EGF-type repeats as well as the fibrinogen globe are supposed to play a role in the formation of tumor blood vessels. 80 The TN-C-induced generation of tumor blood vessels could be related to the binding to endothelial cells 81 and its stimulating effect on this cell type.…”
Section: Tn-c In Tumor Angiogenesismentioning
confidence: 94%
See 1 more Smart Citation
“…Within one tumor different phenotypes like incipient proliferation of endothelial cells or sarcomatous structures are found. 77 Especially the alternatively spliced domains TNfnC 78,79 and TNfnA2 38 could be found highly up-regulated in glioma blood vessels, but also the EGF-type repeats as well as the fibrinogen globe are supposed to play a role in the formation of tumor blood vessels. 80 The TN-C-induced generation of tumor blood vessels could be related to the binding to endothelial cells 81 and its stimulating effect on this cell type.…”
Section: Tn-c In Tumor Angiogenesismentioning
confidence: 94%
“…86 Additionally to the high expression of TN-C in glioma blood vessels the known receptor for TN-C, integrin a v, is found in elevated levels in glioma tissue, as well as the protein periostin. 77 Periostin was detected as a promoter of TN-C incorporation into the ECM and to organize the architecture of the ECM. 87 For murine pancreatic neuroendocrine tumorigenesis it could be recently shown that the composition of upregulated matrisomal genes in pericytes could be correlated to genes overexpressed also in glioma.…”
Section: Tn-c In Tumor Angiogenesismentioning
confidence: 99%
“…IGFBP7 is induced in endothelial cells in response to tumourderived TGFβ and enhances tube formation, suggesting that IGFBP7 may contribute to glioblastoma angiogenesis [55]. Mustafa et al [56] compared protein expression in isolated glioblastoma vessels with expression in angiogenic endometrial vessels through LTQ Orbitrap MS and found 29 genes to be specifically expressed in the glioblastoma vessels including tenascin C, Nid1, Nid2 and integrin α5. These genes were also identified as glioblastoma vessel markers in a recent study in my laboratory [23].…”
Section: Vascular Abnormalization Is Associated With Distinct Gene Exmentioning
confidence: 99%
“…TGF-β plays a dual role in angiogenesis by orchestrating a switch from vascular inhibition to pro-angiogenic activity [57]. In particular, there is evidence that TGF-β1 induced angiogenesis acts with VEGF to mediate apoptosis of excessive vascular sprouts and may even be required for initial sprouting from an existing vascular network [8, 9].…”
Section: Introductionmentioning
confidence: 99%